Comparison between Different Groups of Vegetarianism and Its Associations with Body Composition: A Literature Review from 2015 to 2021 - Fontes, Tatiana; Rodrigues, Luis Monteiro; Ferreira-Pêgo, Cíntia (Nutrients, 2022)
Background: Vegetarian and vegan diets have become increasingly popular in the last years for many reasons, including their association with various health benefits when compared to omnivorous diets. The main objective of the study was to collect recent (2015–2021) scientific evidence for potential implications between a vegetarian/vegan diet and an individuals’ body composition. Methods: A literature search was conducted in PubMed, with 22 studies selected for inclusion in our collective evaluation. Of the 22 studies included, there were 12 randomized controlled trials, 1 nonrandomized controlled trial, 1 comparative study, and 8 cross-sectional. The overall sample included in this study consists of 436,178 participants, 10,090 of whom were vegetarians, 5044 vegans, and 421,044 omnivores. Results: Most studies, 17 out of 22, reported a significant positive relationship between a plant-based diet and body composition. Conclusion: There is scientifically sound evidence that vegan or vegetarian diets are associated with weight and body mass index reduction and, in some cases, fat mass distribution changes.